Efficacy of various Platelet concentrates on the rate of Orthodontic tooth movement – A Systematic Review and Meta-Analysis.: Life Sciences-Nursing - Ammayappan, Pavithranand; Natarajan, Prabhu Manickam; C, Vijayadhith (International Journal of Life Science and Pharma Research, 2023)
With increased interest in reducing the average duration of Orthodontic treatment, various techniques for accelerating tooth movement have been extensively researched. Studies have shown conflicting results with various Platelet Concentrates (PCs). Hence this review aimed to evaluate and gather evidence of the effectiveness of Platelet concentrates (PRP/PRF) during orthodontic extraction space closure about the space closure rate and the time required for and the angular measurements of the tooth movement during space closure. The electronic databases of Cochrane CENTRAL, PubMed, Scopus, Web of Science, Embase, and Google Scholar were searched up to June 2021. The criteria for selection were Randomised Controlled Trials (RCTs) comparing the use of PCs with that of no intervention/placebo during canine retraction or retraction of anterior teeth. All other studies were excluded. Two reviewers performed the entire process of study selection, extraction of data, and quality assessment independently. Cochrane’s ROB2 tool was used for quality assessment in the studies selected. The quantitative analysis of the studies was performed with the use of Review Manager (RevMan5). Eight RCTs met the inclusion criteria and were included for the qualitative synthesis in this review. Of these, five RCTs were included in the quantitative analysis. The results indicated an insignificant increase in the rate of tooth movement with the administration of the PCs (0.13 mm more Tooth movement; 95% CI = -0.17 – 0.43; p = 0.40). No differences were also found in the change of canine inclination and amount of canine rotation. Quantitative synthesis of the selected five studies (3 studies had a low Risk of Bias) reveals no statistically significant difference in the rate of tooth movement with the use of PCs. The results of this analysis should be interpreted with caution owing to the existence of heterogeneity. Limited evidence suggests an actual reduction in the overall treatment duration. Future studies should be aimed at standardizing the protocol for preparing and administering the PCs. This review did not receive any funding.Trial registration number: PROSPERO CRD42021241221